Perkembangan Hukum Keluarga Islam Pada Masa Kerajaan di Indonesia - Ilman Huda, M. Al Amin; Holik, Abd. (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
This article discusses three Islamic kingdoms in Indonesia, namely the Aceh Darussalam Kingdom (1496 AD – 1903), the Islamic Mataram Kingdom (1588-1681), and the Gowa-Tallo Kingdom (1591-1669). The main focus is on the government system, judiciary, and legal sources used by the three kingdoms. The Kingdom of Aceh Darussalam, located in Aceh, Sumatra, has an organized and efficient government system. They developed a military education system, fought European imperialism, and had a strong commitment to Islam. Sources of law include custom, law, qanun, reusam, and the book of fiqh, with the Sultan as the supreme law maker. The Islamic Mataram Kingdom, established in Java, combined Hindu-Islam through Islamization. The government system integrates Islamic law and Javanese customs. Sultan Agung implemented Islamic law in the judiciary, incorporating civil and criminal law, and appointed individuals with an understanding of Islam in the judiciary. The Kingdom of Gowa-Tallo in Sulawesi adopted Islam as its official religion in 1605 AD. The King of Gowa-Tallo appointed sharia officials equivalent to adek officials, established a level III court, and managed zakat and alms funds to support Islamic religious justice. These three kingdoms demonstrate the importance of Islam in the government, justice and legal systems of Indonesia's past, combining religious teachings with local traditions to create a system that functioned effectively.